2019
DOI: 10.1042/bsr20190546
|View full text |Cite
|
Sign up to set email alerts
|

Low concentration of rutin treatment might alleviate the cardiotoxicity effect of pirarubicin on cardiomyocytes via activation of PI3K/AKT/mTOR signaling pathway

Abstract: Cancer is the leading cause of deaths around the world, especially in low- and middle- income countries. Pirarubicin (THP) is an effective drug for treatment of cancer, however, there still exists cardiotoxic effects of THP. Rutin is a kind of antioxidative compound extracted from plants, and might be a protective compound for cardiomyocytes. Phosphatidylinositol 3-hydroxy kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) signaling pathway is critical for cellular survival, proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…Cisplatin causes cardio-toxic effects by oxidative stress and decrease in antioxidant enzymes [11]. Rutin has been previously reported for bene cial protective effects against variety of drug induced toxicities including doxorubicin and cisplatin induced cardiac toxicity [12][13][14]. The protective effects of rutin trihydrate observed in our current study mostly likely occurred due to its profound anti-oxidant properties.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Cisplatin causes cardio-toxic effects by oxidative stress and decrease in antioxidant enzymes [11]. Rutin has been previously reported for bene cial protective effects against variety of drug induced toxicities including doxorubicin and cisplatin induced cardiac toxicity [12][13][14]. The protective effects of rutin trihydrate observed in our current study mostly likely occurred due to its profound anti-oxidant properties.…”
Section: Discussionsupporting
confidence: 50%
“…Increase in oxidative stress and decrease in antioxidant enzymes are linked with cardio-toxic effects of cisplatin [11]. Rutin has been reported for bene cial protective effects against variety of drug induced toxicities including doxorubicin and cisplatin induced cardiac toxicity and memory de cits [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that rutin can increase PI3K, Akt, and mTOR, and decrease NF‐κB expression. The involvement of rutin in cardiac function may be through activation of PI3K/Akt/mTOR and inhibition of the NF‐κB pathway [ 22 ] (Figure 3).…”
Section: Protective Effects Of Natural Compounds Against Cytotoxic Drmentioning
confidence: 99%
“…6,7 Thus, novel therapeutic agents that help combat THP-induced cardiotoxicity are required. 6,7 Thus, novel therapeutic agents that help combat THP-induced cardiotoxicity are required.…”
Section: Introductionmentioning
confidence: 99%
“…However, patients who receive THP treatment can still suffer significant cardiac injuries. 6,7 Thus, novel therapeutic agents that help combat THP-induced cardiotoxicity are required.…”
Section: Introductionmentioning
confidence: 99%